Gambaran Intervensi Koroner Perkutan Primer pada Pasien Infark Miokard Akut dengan Elevasi Segmen ST di RSUP Prof Dr. R. D. Kandou Manado Periode Januari â€“Desember 2017 - Lolaen, Cristina; Rampengan, Starry H.; Pangemanan, Janry A. (e-CliniC, 2018)
Abstract: Acute coronary syndrome (ACS) is one of the main problems in the cardiovascular field due to its increasing numbers of morbidity and mortality. One of the classifications of ACS is acute myocardial infarction (AMI) with ST segment elevation (STEMI). Intervention that can be done mechanically for AMI with STEMI is primary percutaneous coronary intervention (PPCI). This study was aimed to determine the profile of PPCI in patients with AMI-STEMI at Prof. Dr. R. D. Kandou Hospital Manado from January to December 2017. This was a descriptive observational study with a retrospective approach using medical record data of AMI-STEMI patients. Samples were obtained by using consecutive sampling technique. The results showed that of the total 132 STEMI patient there were 63 samples that fulfilled the criteria. Most patients were male as many as 57 people (90.5%), aged 45-49 years as many as 17 people (27%), BMI 18,5-24,9 (normal) as many as 42 people (66.6%). Of 63 samples, 24 patients had only one risk factor (38.1%), with hypertension as the most common risk factor in 45 people (71.4%). Among patients that underwent PPCI, the PPCI was predominantly performed on the 3-<6 hours after onset as many as 23 people (36.5%). Conclusion: Among patients that underwent PPCI, male patients were much more common than female, and hypertension was the most risk factor of ACS. Most PPCIs were performed on the 3-<6 hours after onset.Keywords: AMI, STEMI, PPCIÂ Abstrak: Sindrom koroner akut (SKA) merupakan salah satu masalah utama kardiovaskular karena menyebabkan tingginya angka morbiditas dan mortalitas. Salah satu klasifikasi dari SKA ialah infark miokard akut dengan elevasi segmen ST (IMA-EST). Tindakan yang dapat dilakukan secara mekanis yaitu intervensi koroner perkutan (IKP) primer. Penelitian ini bertujuan untuk mengetahui gambaran IKP primer pada pasien IMA-EST di RSUP Prof. DR. R.D. Kandou Manado periode Januari-Desember 2017. Jenis penelitian ialah deskriptif observasional dengan pendekatan retrospektif menggunakan data rekam medik pasien IMA-EST. Teknik pengambilan sampel yaitu consecutive sampling. Hasil penelitian memper-lihatkan dari total 132 pasien IMA-EST didapatkan 63 sampel yang memenuhi kriteria. Frekuensi terbanyak pada jenis kelamin laki-laki sebanyak 57 orang (90,5%), kelompok usia 45-49 tahun 17 orang (27%), IMT 18,5-24,9 (normal) 42 orang (66,6%). Dari jumlah 63 sampel, terbanyak memiliki 1 faktor risiko yaitu 24 orang (38,1%), dengan hipertensi sebagai faktor risiko terbanyak pada 45 orang (71,4%). Pada pasien yang menjalani IKP primer terbanyak dilakukan pada awitan gejala 3-<6 jam yaitu 23 orang (36,5%). Simpulan: Pasien berjenis kelamin laki-laki paling banyak menjalani IKP primer, dengan hipertensi merupakan faktor risiko PJK terbanyak dan IKP primer terbanyak dilakukan pada awitan 3-<6 jam.Kata kunci: IMA-EST, IPK primer